Knowledge about monkeypox among health professionals, Lima-Peru - Navarrete-Mejía, Pedro Javier (2022)
Background: the SARS-CoV 2 pandemic showed us that we were not prepared, that it will not happen again. Objective: to know the level of knowledge about the etiology, symptoms, treatment and prevention of monkeypox disease in health professionals. The study: observational-descriptive, included 251 health professionals, both sexes, voluntary participation. A questionnaire was developed including the variables age, sex and questions about the monkeypox disease, descriptive analysis of the data. Finding: low knowledge about the etiology, symptoms, treatment and prevention of the disease. Less knowledge about forms of contagion (21.9%), incubation time (21.9%), characteristics of the virus (24.3%) and laboratory diagnosis (25.1%); greater knowledge about contagiousness in the incubation period (61.0%), presence of rashes as a characteristic of the disease (53.8%) and lack of specific treatment (52.2%). Conclusion: low knowledge; The formulation of strategies is urgently needed to be able to face possible cases, if necessary.